Brain TSPO expression is associated with plasma pTau181 & pTau231 across the AD spectrum. (20th December 2022) - Rahmouni, Nesrine; Therriault, Joseph; Tissot, Cécile; Lussier, Firoza Z; Stevenson, Jenna; Stevenson, Alyssa; Servaes, Stijn; Ashton, Nicholas J.; Kvartsberg, Hlin; Arias, Jaime Fernandez; Wang, Yi‐Ting; Kang, Min Su; et al.
Abstract: Background: Microglial activation is an important component of the immune response in the brain of AD patients and has been shown to follow a similar propagation pattern to tau tangle accumulation. However, it is unclear to what extent cerebral microglial activation is associated with biofluid concentrations of phosphorylated tau (pTau). The objective was to investigate whether concentrations of pTau181 and pTau231 are correlated with microglial activation indexed by [ 11 C]PBR28 PET across the AD spectrum. Method: The present study was conducted in a population of 130 individuals from the Translational Biomarkers of Aging and Dementia (TRIAD) cohort: 20 young cognitively unimpaired, 65 cognitively unimpaired elderlies, 31 with mild cognitive impairment and 14 with AD dementia. Participants were evaluated with blood biomarkers and [ 11 C]PBR28 PET. Plasma pTau181 and pTau231 concentrations were quantified using a Simoa assay. Microglial activation was assessed via [ 11 C]PBR28 PET, standardized uptake value ratios (SUVRs) were calculated between 0 and 90 minutes post‐injection, using cerebellum grey matter as the reference region. Voxel‐based regression models evaluated the relationship between plasma pTau181 and pTau231 with neuroinflammation as assessed by PET, correcting for age and sex. Result: In the present study, positive correlations were found between concentrations of both pTau181 and pTau231 and neuroinflammation indexed by PET‐imaging. Voxel‐level analyses indicated that these associations prenominated in regions of the default mode network including the precuneus, posterior cingulate cortex and medial prefrontal cortex. These regional associations survived corrections for multiple comparisons. Conclusion: Peripheral phosphorylated tau is associated with neuroinflammation in brain regions associated with AD. Our findings highlight the importance of neuroinflammation in the pathogenesis of AD.